The Relationship between Marital Satisfaction and Spiritual Well-Being of Chinese Older Adults: The Mediating Effect of Psychological Security and Aging Expectations - Longxing Tang; Yachi Yang; Zhiwei An; Yalian Huang; Ping Tang (Behavioral Sciences)
This study explores the relationship between marital satisfaction and spiritual well-being in older adults and the role of psychological security and aging expectations in older adult relationships. A convenient sample cross-sectional research method collected data from 367 older adults in Sichuan Province, China. A chain mediation model was constructed using quantitative analysis methods to test the relationship between marital satisfaction and older adults’ spiritual well-being and the potential mediating roles of psychological security and aging expectations. The research conclusions are as follows: marital satisfaction positively correlates with spiritual well-being, and psychological security and aging expectations play independent chain mediating roles.